Education, productivity, and inequality: The East African natural experiment - Knight, J; Sabot, R (Oxford University Press, 1990)
Drawing on the experiences of Kenya and Tanzania, investigates how the expansion of the educational system affects productivity and the growth and distribution of income. Explains that Kenya and Tanzania, with their similar colonial background, natural resources, and economic structure, but markedly divergent educational policies, constitute a "natural experiment." Obtains measures of both reasoning ability and cognitive skill from surveys of representative samples of urban wage employees, allowing the development of a model to evaluate the human capital, screening, and credentialist interpretations of the link between educational attainment and earnings. Evaluates competing explanations for the steeper earnings-experience profile of the more educated. Estimates the effects of country differences in the quantity and quality education on output. Analyzes occupation as an important intermediary between education and earnings. Isolates the effect that institutional intervention by the government has on the wage structure. Measures the responsiveness of the wages of secondary and primary leavers to changes in their relative supply. Examines how levels of inequality change in response to changes in the composition of the workforce that result from educational expansion. Considers the equality of the distribution of school places in Kenya and Tanzania. Explores whether the expansion of secondary enrollment in Kenya, and the contrasting situation in Tanzania, have affected the degree of intergenerational mobility and the process of class formation. Examines methodological and policy issues in the cost-benefit analysis and in the financing of secondary education. Considers the implications of the findings for future research and the extent to which the results can be generalized to other countries and situations. A companion volume, Education, Work and Pay in East Africa, describes the economies and education systems of Kenya and Tanzania, and contains an annotated set of cross-tabulations and other summary statistics based on East African surveys. Knight is a Senior member of the research staff at the Institute of Economics and Statistics. Sabot is Professor of Economics at Williams College. Index.